Թեք վերջնաբաղադրիչով բառեր հայերէնի մէջ - Ֆիշէնկճեան, Ա. Ա.
Слово թեք [tcekc] ‘накломмый’ грамматически является прилагательным и наречием. При помощи которого образуют новые слова, но их мало как в восточноармянских, так и в западноармянских словарях. Их не всегда можно рассматривать как новые слова. The word թեք [tcecc] 'oblique' is grammatically an adjective and an adverb. With the help of which new words are formed, but they are few in both Eastern and Western Armenian dictionaries.They may not always be considered as new words.
Keywords: Լեզվաբանություն